INCORPORATING TEACHING EFL READING INTO THE MODEL OF LEARNING FROM PRESENTATION FOR INDONESIAN STUDENTS - Nasir Nasir (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
Model of teaching delineates learning materials which are enacted by learners. Not only is teaching reading as a receptive skill; teaching reading is also as an integrated skill. This study aimed at describing incorporating teaching EFL reading as a receptive skill into Model of Learning from Presentation (MLP) as visual and oral–based teaching at teachers’ training of elementary school of Nahdlatul Ulama University of Lampung, Indonesia. To investigate, questionnaire and interview were deployed as research instruments in this descriptive qualitative study. The findings of questionnaires, which explored three aspects including graphic organizer as a visual aspect, oral presentation as a oral aspect, and students’ perceptions for each aspect, to 24 students showed (1) almost all students (87%) stated MLP enabled them to learn graphic organizers which induced ease of presentation, (2) many students (75%) stated MLP enabled them to practice oral presentation which could foster their speaking and writing skills, (3) all students (100%) stated MLP reinforced their responsibility for material mastery and presentation delivery. These were confirmed by the findings of interviews to 5 students that revealed (1) their needs for graphic organizer in MLP to elude inaccurate diagram construction; (2), their needs for oral presentation in MLP to enhance linguistic knowledge and text comprehension, (3) their needs of MLP to deliver learning materials